2022
DOI: 10.3390/ma15041385
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Cooling Rate on the Microstructure Evolution and Mechanical Properties of Ti-Microalloyed Steel Plates

Abstract: Ti-bearing microalloyed steel plates with a thickness of 40 mm were subjected to ultra-fast cooling (UFC) and traditional accelerate cooling after hot-rolling, aiming to investigate the effect of cooling rate on the microstructure and mechanical properties homogeneity, and thus obtain thick plates with superior and homogeneous mechanical properties. Yield strength, tensile strength, and elongation were 642 MPa, 740 MPa, 19.2% and 592 MPa, 720 MPa and 16.7%, respectively, in the surface and mid-thickness of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The problem of increasing the homogeneity of the composition, structure, and properties of metal in modern metallurgical technologies is one of the most important, since it largely controls the properties and quality of steel. It applies to all stages of the metal, from smelting to the production of finished metal products [20,21,32,33,[97][98][99]. For example, in [100], based on the testing of samples taken from four places within the product, i.e., front-centre, back-centre, centre-centre and centre-edge, it was shown that there was at least 10% variation in mechanical properties within one roll.…”
Section: Effect Of Excess Phases On the Homogeneity Of Composition An...mentioning
confidence: 99%
See 1 more Smart Citation
“…The problem of increasing the homogeneity of the composition, structure, and properties of metal in modern metallurgical technologies is one of the most important, since it largely controls the properties and quality of steel. It applies to all stages of the metal, from smelting to the production of finished metal products [20,21,32,33,[97][98][99]. For example, in [100], based on the testing of samples taken from four places within the product, i.e., front-centre, back-centre, centre-centre and centre-edge, it was shown that there was at least 10% variation in mechanical properties within one roll.…”
Section: Effect Of Excess Phases On the Homogeneity Of Composition An...mentioning
confidence: 99%
“…In the work [98], sheet steel with the composition, wt.%: 0.15 C-0.98 Mn-0.28 Si-0.02 Al-0.08 Ti-0.0027 N with a thickness of 40 mm was studied. It was found that the near-surface layer and the mid-thickness region differed both in grain size and in the size of titanium carbide precipitates.…”
Section: Effect Of Excess Phases On the Homogeneity Of Composition An...mentioning
confidence: 99%
“…In recent years, with the development of steel production technology towards high quality, efficiency, low consumption, and low cost, the microalloyed element Ti has been increasingly valued. 1 The low cost and excellent performance of Ti microalloyed steel are increasingly evident, which makes Ti microalloyed steel have broad application prospects. 2 Due to the high sensitivity of TiC precipitation to temperature and cooling rate, it is easy to cause fluctuations in the mechanical properties of different parts of the steel plate.…”
Section: Introductionmentioning
confidence: 99%